Transfer Of Functions Of Agriculture To Non Agriculture Land Under Government Regulation Number 1 Of 2011 Concerning The Establishment And Transfer Function Of Agricultural Land Sustainable The Food - Indana Fawaizah; Arif Zaenal Abidin; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
In this study concluded that: Implementation of agricultural land conversion to non agriculture through several stages, namely: a. The applicant submits the application permit conversion of land attached with the above requirements. b. Setting and Planning Section of Land examination whose results land noted in the minutes of technical considerations arrangement of land. c. The committee did Meetings Land examination, the results are set forth in the Minutes for consideration demolition permit over the land / Land Use Change Permit (IPPT) by the Head of the Land Office. d. Issuance of land conversion permits Decree (SK Land Use Change Permit). e. Delivery of the Decree of the land conversion permit (SK Land Use Change Permit). Act No.41 of 2009 on the Protection of Agricultural Land Sustainable Food, Government Regulation No. 1 of 2011 on the Establishment and Transfer Function Agricultural Land Sustainable Food has been able to balance the food sector while Act No. 26 of 2007 on Spatial Planning, has not fully balance the conversion of agricultural land to non-agricultural because there is a review of every five (years) 1 (one time. Implementation of the transformation of agricultural land to non-agricultural constrained because some of the following: a. Refusal of requests for land use only verbally. b. The term of service of technical considerations of land is 13 (thirteen) days. But in practice it can reach 3 months. c. The calculation of the cost of land use not in accordance with the applicable regulation.Keywords: Judicial Review; Over the function of Land; Agriculture and Non-Agriculture Land.